Domain Semirings United - Fahrenberg, Uli; Johansen, Christian; Struth, Georg; Ziemiański, Krzysztof (Acta Cybernetica, 2022)
Domain operations on semirings have been axiomatised in two different ways: by a map from an additively idempotent semiring into a boolean subalgebra of the semiring bounded by the additive and multiplicative unit of the semiring, or by an endofunction on a semiring that induces a distributive lattice bounded by the two units as its image. This note presents classes of semirings where these approaches coincide.